Measuring Impact. Making Use of the Portfolio: Organizational Learning at USAID - Peabody, Shawn (USAID, 2015)
This technical analysis explores previous and ongoing social learning efforts, best practices, challenges, and lessons in USAID as a foundat ion for improving the implementation and design of the Agency’s forest ry and biodiversity programs. This analysis is particularly relevant a s the Bureau of Economic Growth, Education and the Environment’s Offic e of Forestry and Biodiversity (E3/FAB) begins to develop a Cross-Miss ion Learning Program under the Measuring Impact initiative, a five-yea r activity to promote the adoption of best practices in the USAID prog ram cycle among Missions using biodiversity funds. The findings report ed in this document can help inform the overall design and structure o f the Learning Program and provide insight into possible challenges an d best practices.